Pulsed arterial spin labelling at ultra-high field with a B1+-optimised adiabatic labelling pulse - Zimmer, Fabian (Magnetic resonance materials in physics, biology and medicine, 2016)
Objective: Arterial spin labelling (ASL) techniques benefit from the increased signal-to-noise ratio and the longer T 1 relaxation times available at ultra-high field. Previous pulsed ASL studies at 7 T concentrated on the superior regions of the brain because of the larger transmit radiofrequency inhomogeneity experienced at ultra-high field that hinders an adequate inversion of the blood bolus when labelling in the neck. Recently, researchers have proposed to overcome this problem with either the use of dielectric pads, through dedicated transmit labelling coils, or special adiabatic inversion pulses. Materials and methods: We investigate the performance of an optimised time-resampled frequency-offset corrected inversion (TR-FOCI) pulse designed to cause inversion at much lower peak B 1 + . In combination with a PICORE labelling, the perfusion signal obtained with this pulse is compared against that obtained with a FOCI pulse, with and without dielectric pads. Results: Mean grey matter perfusion with the TR-FOCI was 52.5 ± 10.3 mL/100 g/min, being significantly higher than the 34.6 ± 2.6 mL/100 g/min obtained with the FOCI pulse. No significant effect of the dielectric pads was observed. Conclusion: The usage of the B 1 + -optimised TR-FOCI pulse results in a significantly higher perfusion signal. PICORE-ASL is feasible at ultra-high field with no changes to operating conditions.